Spaghetti Technique Versus Wide Local Excision for Lentigo Maligna Affecting the Head and Neck Regions: Surgical Outcome and Descriptive Analysis of 79 Cases From a Single Practice Cohort - Manel Martinez-Molina; Nina Richarz; Ane Jaka; Juli Bassas-Vila; Verónica Mora-Fernández; Ariadna Quer Pi-Sunyer; Sebastian Podlipnik; José Manuel Carrascosa; Aram Boada (Mattioli1885, 2023)
Introduction: Lentigo maligna is a subtype of melanoma in situ that typically affects the head and neck region with an increasing incidence. Margin-controlled techniques, such as spaghetti technique (ST), have gained popularity over wide local excision (WLE) with a margin of 5 mm. Objectives: To evaluate the outcomes of lentigo maligna cases in the head and neck area treated by either WLE or ST in a tertiary referral hospital. The secondary goal was to describe the demographic and clinical characteristics of our series. Methods: Cohort study of patients diagnosed with lentigo maligna on the head and neck region between January 2014 and February 2022 in a tertiary hospital. Results: In total, 79 lentigo maligna were studied, corresponding to 77 patients. Fifty-three lesions (67%) were treated with WLE and 26 (33%) with ST. The mean age of the patients was 73 years and 58% were men. Most of the tumors were located on the cheek (50%) and mean lesion diameter was 2.2 cm for the ST group and 1.2 cm for the WLE group. Mean duration follow-up was 44 months. There were two local recurrences in the WLE group (2/53; 3.7%) and none in the ST group. Conclusions: Both WLE and ST are appropriate surgical approaches for lentigo maligna. ST offers an efficient alternative to Mohs surgery for treating lentigo maligna in the head and neck area, especially when guided by reflectance confocal microscopy.